2009
DOI: 10.1073/pnas.0903851106
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular biosynthesis of cysteinyl leukotrienes in vivo during mouse peritoneal inflammation

Abstract: Leukotrienes (LTs) are lipid mediators of inflammation formed by enzymatic oxidation of arachidonic acid. One intriguing aspect of LT production is transcellular biosynthesis: cells expressing 5-lipoxygenase (5LO) form LTA4 and transfer it to cells expressing LTA4 hydrolase (LTA4H) or LTC4 synthase (LTC4S) to produce LTB4 or LTC4. This process has been demonstrated in vivo for LTB4, but not for cysteinyl LTs (cysLTs). We examined transcellular cysLT synthesis during zymosan-induced peritonitis, using bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…The epithelium is often overlooked as a regulator of eicosanoids, because the terminal synthetic enzymes for the major eicosanoids implicated in asthma are predominantly expressed in leukocytes; however, structural cells serve as an important source of AA via transcellular metabolism (51). We found that sPLA 2 -X serves as a key regulator of AA release in mTECs and that the PLa2g10 knockout had a larger effect on AA release than inhibition of cPLA 2 a, which is generally believed to be the dominant regulator of AA release in epithelial cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium is often overlooked as a regulator of eicosanoids, because the terminal synthetic enzymes for the major eicosanoids implicated in asthma are predominantly expressed in leukocytes; however, structural cells serve as an important source of AA via transcellular metabolism (51). We found that sPLA 2 -X serves as a key regulator of AA release in mTECs and that the PLa2g10 knockout had a larger effect on AA release than inhibition of cPLA 2 a, which is generally believed to be the dominant regulator of AA release in epithelial cells (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, they express LTA 4 hydrolase and LTC 4 synthetase enzymes, which can generate LTB 4 and LTC 4 , respectively, from exogenous LTA 4 . In addition, other studies have identified the transcellular mode of cysteinyl-LT biosynthesis (8,52) by uptake of LTA 4 , which is secreted from neighboring activated peripheral blood leukocytes after their adhesion to vascular endothelium (53). Consequently, a direct role of endothelial cells as an independent source of LT has not been widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…LTE 4 , the most abundant cys-LT at sites of inflammation due to its stability (7,8), was only a weak agonist for the CysLT 1 R and CysLT 2 R in studies with transfectants (3, 4), suggesting that it might lack agonist activity. In contrast, pretreatment with LTE 4 , but not LTC 4 or LTD 4 , enhanced the response of guinea pig trachea (9) or human bronchial smooth muscle to histamine (10).…”
mentioning
confidence: 97%
“…The type 1 cys-LT receptor (CysLT 1 R) is the high affinity receptor for LTD 4 , whereas the type 2 receptor (CysLT 2 R) can bind both LTC 4 and LTD 4 with one-log less affinity than that of CysLT 1 R for LTD 4 in transfected cells (3, 4). The cys-LTs are mediators of bronchial asthma on the basis of their potent bronchoconstrictive activity via the CysLT 1 R in pharmacologic studies and the clinical effectiveness of CysLT 1 R antagonists (5, 6).LTE 4 , the most abundant cys-LT at sites of inflammation due to its stability (7,8), was only a weak agonist for the CysLT 1 R and CysLT 2 R in studies with transfectants (3, 4), suggesting that it might lack agonist activity. In contrast, pretreatment with LTE 4 , but not LTC 4 or LTD 4 , enhanced the response of guinea pig trachea (9) or human bronchial smooth muscle to histamine (10).…”
mentioning
confidence: 99%